PH variability off Goa (eastern Arabian Sea) and the response of sea urchin to ocean acidification scenarios. (16th September 2020) - Shetye, Suhas S.; Naik, Hema; Kurian, Siby; Shenoy, Damodar; Kuniyil, Nandakumar; Fernandes, Michelle; Hussain, Afreen
Abstract: The increasing atmospheric CO2 concentration in the last few decades has resulted in a decrease in oceanic pH. In this study, we assessed the natural variability of pH in coastal waters off Goa, eastern Arabian Sea. pHT showed large variability (7.6–8.1) with low pH conditions during south‐west monsoon (SWM), and the variability is found to be associated with upwelling rather than freshwater runoff. Considering that marine biota inhabiting dynamic coastal waters off Goa are exposed to such wide range of natural fluctuations of pH, an acidification experiment was carried out. We studied the impact of low pH on the local population of sea urchin Stomopneustes variolaris (Lamarck, 1816). Sea urchins were exposed for 210 days to three treatments of pHT : 7.96, 7.76 and 7.46. Our results showed that S. variolaris at pHT 7.96 and 7.76 were not affected, whereas the ones at pHT 7.46 showed adverse effects after 120 days and 50% mortality by 210 days. However, even after exposure to low pH for 210 days, 50% organisms survived. Under low pH conditions (pHT 7.46), the elemental composition of sea urchin spines exhibited deposition of excess Sr 2+ as compared to Mg 2+ ions. We conclude that although the sea urchins would be affected in future high CO2 waters, at present they are not at risk even during the south‐west monsoon when low pH waters reside on the shelf.